Agricultural expansion and deforestation: modelling the impact of population, market forces and property rights - Angelsen, A. (1999)
This paper compares four different modelling approaches to agricultural expansion and deforestation, and explores the implications of assumptions about the household objectives, the labour market, and the property rights regime. A major distinction is made between population and market based explanations. Many of the popular policy prescriptions are based on the population approach, assuming subsistence behaviour and limited market integration. Within a more realistic-particularly for the long term effects-market approach, well-intentioned policies such as agricultural intensification programmes may boost deforestation. Many forest frontier contexts are also charaterized by forest clearing giving farmers land rights. Deforestation becomes an investment to the farmer and a title establishment strategy. Land titling and credit programmes may therefore increase deforestation